Preliminary Evaluation of The Cyprus Erythemal Irradiance Forecasting System - Charalampous, Georgia; Fragkos, Konstantinos; Nisantzi, Argyro; Fountoulakis, I.; Papachristopoulou, Kyriakoula; Hadjimitsis, Diofantos G.; Kazadzis, S. (My University, 2025)
Cyprus experiences some of the highest levels of solar radiation in Europe, which presents both opportunities for solar energy and risks associated with ultraviolet (UV) exposure. In response to the need for better public awareness and UV protection measures, the Cyprus Erythemal Irradiance Forecasting System (CERYFOS) was developed to forecast the UV Index (UVI) across the island. This paper presents a preliminary evaluation of the CERYFOS model’s accuracy by comparing forecasted UVI values with ground-based measurements taken from December 2023 to September 2024. The model’s predictions were assessed against data from a Kipp & Zonen SUV-E actinometer and a Bentham DMc150 spectrophotometer, operating in Limassol. Results showed that the system performs well under clear-sky conditions, achieving a Root Mean Squared Error (RMSE) of 0.36[UVI units] and minimal bias. The study also highlights the influence of aerosol optical depth (AOD) and ozone variability on forecast accuracy. These findings underline the need for model refinements, particularly concerning cloud impact and atmospheric parameter representation. With further improvements, CERYFOS has the potential to enhance public safety by providing accurate UVI forecasts and increasing awareness of UV exposure risks in Cyprus.
Keywords: Cyprus Erythemal Irradiance; Forecasting System